Primary vaginal cancer after hysterectomy for benign conditions: a systematic review of the literature - Qian, Jing; Gracious, Kaoma; Chen, Li; Xu, Song (Frontiers in Oncology, 2024)
Background: Primary vaginal cancer is a rare condition. Some studies have revealed an increased risk of vaginal cancer among patients who have undergone hysterectomy for premalignant and malignant cervical disease.However, there is limited literature available on primary vaginal cancer following hysterectomy for benign conditions.Objectives: This review aimed to investigate available evidence on clinical characteristics, treatments, and outcomes of primary vaginal cancer following hysterectomy for benign diseases. Additionally, we provide a case of a patient who developed primary vaginal cancer 10 years after undergoing hysterectomy for abnormal uterine bleeding.